Regional Food Safety Experts Call for Collaborative Approaches to Transforming Food Safety in African Wet Markets - Awinoh, Martha; Alonso, Silvia (CGIAR Initiative on Resilient Cities, 2023)
Food safety experts from African countries from August 29 – September 2 gathered at the Bellagio Center of the Rockefeller Foundation to deliberate on the future of food safety in the informal food sector in Africa, markets that remain outside formal regulatory oversight which accounts for more than 80% of the continent’s food trade. The session, convened by Rockefeller Foundation in partnership with CGIAR Resilient Cities Initiative and the Global Livestock Advocacy for sustainable Development, gathered food safety experts from seven African countries and technical experts from outside the continent to design novel strategies that will not only enhance food safety but also contribute to food security and livelihoods in informal markets.